2016
DOI: 10.1002/app.44112
|View full text |Cite
|
Sign up to set email alerts
|

Simplified modeling of the electrospinning process from the stable jet region to the unstable region for predicting the final nanofiber diameter

Abstract: Electrospinning allows the production of ultrafine nanofibers through the stretching of a charged polymer jet with an external electrostatic field. In this study, we derived a simplified and accurate model relating the processing parameters, including the solution volumetric flow rate (Q), the applied electric field (E), and the polymer concentration, to the final fiber diameter. The model takes into consideration the jet behavior starting at the stable region and moving to the bending instability region. We v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…With regards to NCD, it has generally been reported that increasing the working distance would result in a decrease in the fiber diameter (and so an increase in the mat thickness) . This has also been observed in our simulations [Figure (b)] and can be explained considering the extended time of travel (or solvent evaporation time).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…With regards to NCD, it has generally been reported that increasing the working distance would result in a decrease in the fiber diameter (and so an increase in the mat thickness) . This has also been observed in our simulations [Figure (b)] and can be explained considering the extended time of travel (or solvent evaporation time).…”
Section: Resultssupporting
confidence: 87%
“…Note that both the increase and decrease of fiber diameter with voltage have been reported in the literature for certain polymers (e.g., Refs. ).…”
Section: Resultsmentioning
confidence: 99%
“…The model involving solution viscosity, evaporation rate, and containing specific charge (electric current divided by the spinning throughput) was introduced in [48,49]. A prediction of a final nanofiber diameter published in [50] is based on the model published in [36]. However, the assumptions limit the model to relatively low polymer-solvent concentrations (<12 wt.%).…”
Section: Introductionmentioning
confidence: 99%
“…and the electrospinning conditions (the electric potential between the capillary tip and the collector, the distance between the tip and the collector, collecting speed, temperature, humidity, and etc.). A validated mathematical model was recently developed to predict the fiber average diameter based on these electrospinning parameters …”
Section: Introductionmentioning
confidence: 99%